Storm on the Horizon: An Inmate Re-authors His Story - Diane Patricia Ketelle (Forum: Qualitative Social Research, 2010)
This paper presents the writing of an inmate, Whispers, who participated in a writing project taught by the author at San Quentin State Prison. The inmate was a student in a class called Write Your Life and it was in that class that he wrote Storm on the Horizon, a story he would author/re-author three times. Through the process of re-authoring he creates a story situated in the real world that ultimately helps him in rendering new meaning from his lived experience. Re-authoring his story allowed Whispers to explore varying perspectives that succeed in making his experience comprehensible. URN: urn:nbn:de:0114-fqs1002287